2022
DOI: 10.1007/s00423-022-02667-6
|View full text |Cite
|
Sign up to set email alerts
|

Robot-assisted transthoracic hybrid esophagectomy versus open and laparoscopic hybrid esophagectomy: propensity score matched analysis of short-term outcome

Abstract: Purpose Minimally invasive en-bloc esophagectomy is associated with a reduction of postoperative morbidity. This was demonstrated for both total minimally invasive and hybrid esophagectomy. However, little is known about any benefits of robotic assistance compared to the conventional minimally invasive technique, especially in hybrid procedures. Methods For this retrospective study, all consecutive patients who had undergone elective esophagectomy with cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…To date, many studies have shown that minimally invasive techniques improve surgical outcomes in patients with gastrointestinal cancers [22][23][24]. Minimally invasive methods used in rectal cancer surgery include laparoscopic techniques, particularly LaTME, as performed from the abdominal access, and TaTME in which abdominal and transanal access are used simultaneously [13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…To date, many studies have shown that minimally invasive techniques improve surgical outcomes in patients with gastrointestinal cancers [22][23][24]. Minimally invasive methods used in rectal cancer surgery include laparoscopic techniques, particularly LaTME, as performed from the abdominal access, and TaTME in which abdominal and transanal access are used simultaneously [13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…To date, many studies have shown that minimally invasive techniques improve surgical outcomes in patients with gastrointestinal cancers 22 24 . Minimally invasive methods used in rectal cancer surgery include laparoscopic techniques, particularly LaTME, as performed from the abdominal access, and TaTME in which abdominal and transanal access are used simultaneously 13 15 .…”
Section: Discussionmentioning
confidence: 99%